Choledochal Cyst Todani Classification Type IC and Choledocholithiasis Presenting as Recurrent Pancreatitis in a 7-Year-Old Girl – A Case Report - Della Sabrina Marta; I Putu Gede Karyana; I Gusti Ngurah Sanjaya Putra; Ni Nyoman Metriani Nesa; Ketut Dewi Kumara Wati; Kadek Deddy Ariyanta (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: Choledochal cyst is an uncommon but important cause of biliary pathology in the pediatric population which can lead to choledocholithiasis and recurrent pancreatitis. High clinical suspicion, comprehensive imaging, and multidisciplinary evaluation are essential for accurate diagnosis and treatment. Definitive management is achieved through surgical intervention. Case: A 7-year-old girl experienced recurrent postprandial right upper quadrant and epigastric pain for three years, with fluctuating pancreatic and hepatic enzymes. Initial ultrasound and magnetic resonance cholangiopancreatography (MRCP) revealed ductal dilatation with biliary sludge, while multislice computed tomography (MSCT) suggested autoimmune pancreatitis, leading to temporary steroid response. Symptoms persisted, and contrast-enhanced magnetic resonance imaging (MRI) demonstrated fusiform common bile duct dilatation with debris, confirming Todani type IC choledochal cyst and choledocholithiasis. She underwent laparoscopic cyst and gallbladder excision with Roux-en-Y hepaticojejunostomy. Intraoperative and histological findings verified sludge, gallstones, and chronic cholecystitis. Discussion: Choledochal cysts should be considered in pediatric recurrent pancreatitis, particularly with biliary obstruction. Advanced imaging and differential diagnosis are crucial. Surgical excision with biliary reconstruction is the treatment of choice. Conclusion: Early recognition and timely surgical intervention are essential to prevent long-term complications.